2018
DOI: 10.1002/jqs.3040
|View full text |Cite
|
Sign up to set email alerts
|

Timing of glacial retreat in the Wicklow Mountains, Ireland, conditioned by glacier size and topography

Abstract: Reconstructing the deglacial history of palaeo-glaciers provides vital information on retreat processes, information which can inform predictions of the future behaviour of many of the world's glaciers. On this basis, this paper presents 170 Schmidt Hammer exposure ages from moraine boulders and glacially sculpted bedrock to reveal the post-Last Glacial Maximum (LGM) history of the Wicklow Mountains, Ireland. These data suggest that large ice masses survived for 4-7 ka after retreat of the Irish Sea Ice Stream… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 103 publications
1
2
0
Order By: Relevance
“…Where we have used SHD at sites that had previously been dated with TCN, we have found good correspondence between the ages derived by both methods within the limits imposed by the respective statistical uncertainties. This suggests that for granite surfaces influenced by the BIIS, SHD is a valid and reliable technique for establishing surface-exposure ages, supporting the conclusions reached in the pioneering work of Tomkins et al (2016, 2018a, 2018b, 2018c). Given that granites are widespread in areas inundated by the BIIS, the potential for rapid field determination of deglaciation age is high and, significantly, the method can be used to extend and refine the developing chronology of deglaciation of the BIIS and YD ice masses.…”
Section: Wider Implicationssupporting
confidence: 80%
See 1 more Smart Citation
“…Where we have used SHD at sites that had previously been dated with TCN, we have found good correspondence between the ages derived by both methods within the limits imposed by the respective statistical uncertainties. This suggests that for granite surfaces influenced by the BIIS, SHD is a valid and reliable technique for establishing surface-exposure ages, supporting the conclusions reached in the pioneering work of Tomkins et al (2016, 2018a, 2018b, 2018c). Given that granites are widespread in areas inundated by the BIIS, the potential for rapid field determination of deglaciation age is high and, significantly, the method can be used to extend and refine the developing chronology of deglaciation of the BIIS and YD ice masses.…”
Section: Wider Implicationssupporting
confidence: 80%
“…By relating the compressive strength of bedrock and boulder surfaces to the degree of surface weathering, relative ages can be proposed for adjacent features (Matthews and Shakesby, 1984; Ballantyne, 1986; Dawson et al, 1986; McCarroll, 1989). This methodology has been adopted by some subsequent studies (McCarroll et al, 1995; Clark and Wilson, 2004; Winkler, 2005; Shakesby et al, 2006), while others have developed the technique into one of high-precision calibrated-age dating (Shakesby et al, 2011; Matthews and Wilson, 2015; Matthews et al, 2015, 2018; Tomkins et al, 2016, 2018a, 2018b, 2018c; Wilson and Matthews, 2016; Wilson et al, 2017). Irrespective of the approach taken, Schmidt-hammer exposure-age dating (SHD) is used for landform age estimation in a wide variety of Quaternary geomorphic contexts—for example, fluvial terraces (Stahl et al, 2013); flood sediments (Matthews and McEwen, 2013); alluvial fans (White et al, 1998); debris flows (Boelhouwers et al, 1999; Wilson and Matthews, 2016); glacial landforms (Winkler, 2005, 2009, 2014; Shakesby et al, 2006; Matthews and Winkler, 2011; Kłapyta, 2013); active and relict rock glaciers (Kellerer-Pirklbauer et al, 2008; Rode and Kellerer-Pirklbauer, 2012; Matthews et al, 2013; Winkler and Lambiel, 2018); pronival ramparts (Matthews et al, 2011, 2017; Matthews and Wilson, 2015); patterned ground (Cook-Talbot, 1991; Winkler et al, 2016), blockstreams (Wilson et al, 2017; Marr et al, 2018), blockfields, boulder lobes, and talus (Wilson and Matthews, 2016; Marr et al, 2018); snow-avalanche impact ramparts (Matthews et al, 2015); rock-slope failures (Clark and Wilson, 2004; Wilson 2007, 2009; Owen et al, 2010; Wilson and Matthews, 2016; Marr et al, 2018; Matthews et al, 2018); fault scarps (Tye and Stahl, 2018); chemically-weathered bedrock surfaces (Owen et al, 2007); raised boulder-dominated shorelines (Sjöberg and Broadbent, 1991; Shakesby et al, 2011); and shore platforms (Knight and Burningham, ...…”
Section: Introductionmentioning
confidence: 99%
“…Ballantyne and Ó Cofaigh, ), suggesting that these and possibly other mountains in north‐west Ireland supported the last remnants of the last Irish Ice Sheet before complete disappearance of glacier ice under the warmer conditions of the Lateglacial Interstadial. The Blue Stack Mountains, along with other mountain areas in Ireland, hosted glaciers during the Younger Dryas Stadial (∼12.9–11.7 ka) (Barr et al ., ; Barth et al ., ; Tomkins et al ., ), but it has not yet been demonstrated that these glaciers had persisted throughout the Lateglacial Interstadial.…”
Section: Discussionmentioning
confidence: 99%